Effect of pilates on regulating menstrual cycle in females with polycystic ovarian syndrome - Sumiya Nazir; Sakshi Sadhu (Elsevier, 2024)
Background: Polycystic Ovarian Syndrome (PCOS) is the most common genetic disorder of the endocrine gland among females during the age of reproduction with an estimated prevalence ranging from 2.2 % to 26 %. It is a typical reason for ovulatory infertility, menstrual dysfunction, and hirsutism. It is a condition in which ovarian cysts develop with a diameter of between two and nine millimeters on one or each ovaries and therefore there is an increase in the volume of one is larger than ten millimeters. Objective: To analyze the effect of pilates on pain and regulation of the menstrual cycle in females with PCOS. Research methodology: A single centered, quasi-experimental study, performed in Lovely Professional University, India on a total of 26 participants suffering from PCOS, based on inclusion and exclusion criteria. After a detailed assessment, the Pilates exercise protocol was given for 3 months i.e. 3 times per week. The readings for pain and regulation were taken at baseline, at the end of 1st, 2nd, and 3rd month using visual analog scale (VAS)and verbal multidimensional score sysem (VMSS). Results: The result findings indicates suggested that there is significant change in the pain (Wilk's Lambda =.117, F(3,23) = 58.109, P < 0.05), variable during the menstruation in PCOS over the time of three months. The menstrual cycles were regularised and the cycle was shifted towards the normal parameters. The VMSS also shows changes that signify that Pilates is effective in PCOS complications. Conclusion: This study concluded that Pilates is effective in reducing the pain in PCOS cases which improves the working ability of the females and also regulates the menstrual cycles which were irregular at the beginning of the treatment.